β-Cyclodextrin/Lecithin: Preparation and Characterization - Peng, Eng Hui; Basri, Hatijah; A. Talip, Balkis (International Journal of Integrated Engineering, 2017)
Lecithin is a fat which is well-known to be obtained from soybeans or egg yolks. It is also taken as a medicine and used as food additive that keep certain ingredients from separating out. Despite of its advantages, lecithin’s application in the industries is restricted due to its sensitivity to heat and light and can be easily oxidized. Hence, this study aims to investigate the effect of β-cyclodextrin (β-CD) in improving the properties of lecithin. The objectives of this study are to prepare and characterize β-CD/lecithin complex followed by study on the influence of β-CD on lecithin’s thermal stability and antioxidant property. Analytical methods employed are fourier transform infra-red (FTIR) spectroscopy for chemistry study, differential scanning calorimetry (DSC) for examination of its thermal stability, DPPH testing for its antioxidant property as well as scanning electron microscopy (SEM) for structural examination. Results from FTIR and SEM analyses confirmed the formation of β-CD/lecithin complex. Thermal stability and antioxidant property of the complexes on the other hand were found to be improved. Of the amount of β-CD studied, it was reported that the best combination of the complex was at β-CD/lecithin ratio of 2:1. The complex of the optimized ratio showed the greatest thermal stability as indicated by its highest melting point (177.8 ºC). The complex also exhibited the greatest antioxidant property as indicated by its highest percentage of DPPH scavenging activity that is 97.1%.